Optimization of soil ph by using calcium carbonate (CaCo3) obtained from seashell waste / Wan Noni Afida Ab Manan and Nur Aain Ab Aziz - Ab Manan, Wan Noni Afida; Ab Aziz, Nur Aain (Universiti Teknologi MARA Cawangan Pahang, 2018)
Calcium carbonate (CaCO3) represents as a by-product from seashell waste. The synthesis of CaCO3 from seashell waste basically can reduce the environmental burden around the seashore in terms of disposal issue. The CaCO3 from seashell waste can be used to stabilize the soil pH when used as a liming agent. Therefore, this study aimed to determine the effect of CaCO3 on soil pH. In this study, seashell wastes were used to obtain the CaCO3compound. The seashell wastes were washed by using household detergent and were crushed using a mortar and pestle to produce powder form. The powder then was analyzed using Fourier Transform Infrared Spectroscopy (FTIR), and Thermogravimetric analysis (TGA) to determine the presence of CaCO3 in seashell waste. Then, soil samples were divided into portions and different amount of CaCO3 from seashell wastes were added based on weight of soil. In this study, 10% to 50% by weights of CaCO3 have been applied on each soil sample. This study found that 50% weight of CaCO3 was the best amount of liming agent because it will stabilize the pH of soil about 7.16. Nevertheless, it should be noted that a comprehensive study is required for more evaluation on soil acidity and effectiveness of seashell waste.